(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
In this study, a technology was developed to obtain a valuable product - terephthalamide - by recycling plastic waste, which causes great harm to the environment. The developed technology consists of two main stages: in the first, terephthalic acid was isolated from plastic waste by hydrolysis, and in the second, terephthalamide was synthesized by reacting this acid with urea. This method is environmentally friendly, relatively inexpensive and highly efficient, and ensures the recycling of waste.